Mala Vicinanza: Female Household-Heads and Proximity to Sex Work in Sixteenth-Century Florence - Kerton-Johnson, Catherine; Whitsit, Brandon; DeSilva, Jennifer Mara (Renaissance and Reformation / Renaissance et Réforme, 2022)
In mid-sixteenth-century Florence the need to fund Santa Elisabetta delle Convertite, the convent sheltering retired sex workers, prompted the introduction of a higher tax on sex workers that offered freedom from identifying signs, geographic restrictions, and the title of meretrice. The result was precisely the diffusion of sex workers across the city that previous legislation has sought to avoid. While legislation identified sex workers’ mala vicinanza (evil proximity) as the justification for creating buffer zones around convents, conversely it also allowed sex workers to live within those buffer zones if they exhibited modestia e bontà (modesty and goodness). This unlikely loophole privileged Santa Elisabetta’s needs while allowing the segregation policy to fail. Using the 1561 decima census, this article tracks the residence of sex workers near to unenclosed female household-heads in an effort to explore the effect of Florentine magistrates’ ambivalence towards poor working women and the segregation policy’s failure.